2020
DOI: 10.1016/j.ijbiomac.2020.08.193
|View full text |Cite
|
Sign up to set email alerts
|

A puzzle piece of protein N-glycosylation in chicken egg: N-glycoproteome of chicken egg vitelline membrane

Abstract: The chicken egg vitelline membrane (CEVM) is an important structure for the transmembrane transport of egg yolk components, protection of the blastodisc, and separation of egg white and egg yolk. In this study, the N-glycoproteome of the CEVM was mapped and analyzed in depth. Total protein of the CEVM was digested, and the glycopeptides were enriched by a hydrophilic interaction liquid chromatography microcolumn and identified by nano liquid chromatography/tandem mass spectrometry. A total of 435 N-glycosylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…5 B). Taken together, these results are consistent with our data for chicken egg N-glycoproteomes showing different N-glycosite numbers (15–28) and locations of chicken mucin-5B from differing egg parts ( Xiao et al, 2020 ). This is an “economical and efficient” mode acquired by living organisms in the long-term evolutionary process: a protein template, yielding multiple structures, with various activities.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5 B). Taken together, these results are consistent with our data for chicken egg N-glycoproteomes showing different N-glycosite numbers (15–28) and locations of chicken mucin-5B from differing egg parts ( Xiao et al, 2020 ). This is an “economical and efficient” mode acquired by living organisms in the long-term evolutionary process: a protein template, yielding multiple structures, with various activities.…”
Section: Resultssupporting
confidence: 92%
“…Heterogeneity is one of the important characteristics of glycosylation. Our research group previously demonstrated the tissue specificity of N-glycosylation ( Geng et al, 2017 ; Xiao et al, 2020 ; Yang et al, 2020 ), though other research groups have reported differing N-glycosites of the same protein. Additionally, heterogeneity in the N-glycosylation of milk protein has been documented.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…7 Recent research has identified 435 N-glycosylation sites on 208 N-glycoproteins in CEVM, and the N-glycans on apolipoprotein B and vitellogenins were supposed to play directional roles in the compounding of peptide chains and lipids. 8 These results, while preliminary, indicated that N-glycosylation has a pivotal role in CEVM protein functions. Okumura et al reported that ZP1 and ZP3 assembled into helical fibrils through strong interactions between their ZP-C domains to form the inner CEVM, while the N-glycan chains on the ZP1 and ZP3 were exposed on the fibril surface.…”
Section: ■ Introductionmentioning
confidence: 81%
“…The supernatant was transferred to hydrophilic interaction liquid chromatography (HILIC) microcolumn and centrifuged at 4,000 × g for 15 min. After three times washing with an enrichment buffer, the glycopeptides were collected from HILIC microcolumn by 10% acetonitrile and dried by vacuum freezing ( Xiao et al, 2020 ). After drying, the glycopeptides were dissolved and digested in 50 μl 50 mM NH 4 CO 3 buffer and 2 μl PNGase F at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%